Body height and swimming performance in 50 and 100 m freestyle Olympic and World Championship swimming events: 1908 - 2016 - Mazzilli, F. (Journal of Human Kinetics, 2019)
There are scattered data showing an increase in the height of Olympic and World Championships swimmers. To identify a possible historical trend, a study of the height of 50 and 100 m freestyle medalists at the Olympic Games and the World Championships between 1908 and 2016 was undertaken. 370 swimmers (186 men and 184 women) were studied. A progressive increase in the height of men`s medalists (r = 0.49, p < 0.001) was detected. With regard to women`s medalists, an increase (r = 0.383, p < 0.01) was also found. To provide a sort of confirmation of this trend, a separate analysis of swimmers achieving new official swimming records, not included in the initial design of the study, was undertaken and a similar and also significant trend was seen in this case in both male and female athletes. This study confirms and greatly expands the observation of other authors, and raises the question of whether the increase in the stature of elite swimmers is simply a reflection of the increase in height of the general population or whether other factors, such as a possible role of training, should be considered. The ethical aspects of an early selection of swimmers perhaps based on the genetic profile of youngsters deserves careful consideration.